Special Admission : How College Sports Recruitment Favors White Suburban Athletes - Hextrum, Kirsten (Book collections on Project MUSE., 2021)
"Special Admission contradicts the national belief that college sports provide upward mobility opportunities. Kirsten Hextrum documents how white middle-class youth become overrepresented on college teams. Her institutional ethnography of one elite athletic and academic institution includes over 100 hours of interviews with college rowers and track & field athletes. She charts the historic and contemporary relationships between colleges, athletics, and white middle-class communities that ensure white suburban youth are advantaged in special athletic admissions. Suburban youth start ahead in college admissions because athletic merit-the competencies desired by university recruiters-requires access to vast familial, communal, and economic resources, all of which are concentrated in their neighborhoods. Their advantages increase as youth, parents, and coaches strategically invest in and engineer novel opportunities to maintain their race and class status. Thus, college sports allow white, middle-class athletes to accelerate their racial and economic advantages through admission to elite universities"--